Redefining the church's mission : towards a contextual and missional ecclesiology in responding to poverty in South Africa - Dreyer, Willem Akkerhuys (Wim) (University of Pretoria, 2025)
Thesis (PhD (Church History and Polity))--University of Pretoria, 2024.